Inés del alma mía (Inés of My Soul) or How to Retrain the Chronicle - Chris Schulenburg (Studies in 20th & 21st Century Literature, 2021)
Among the multitude of lettered discourses employed to communicate Latin America’s marvels during the conquest, the chronicle constituted a particularly effective option. That is, its necessary framing for a Spanish or Portuguese courtly audience with heterogeneous contents mixing history and fiction allowed for a text that served to validate personal service to the crown. Part and parcel of these chronicles’ objectives, of course, consisted of portraying an indigenous population supposedly anxious to accept the work load of the encomienda as well as the Catholic conversions that accompanied this legislated slavery. Moreover, this Eurocentric perspective also boasted an almost completely masculine one. Indeed, with the unique exception of the Baroque “monster” of Catalina de Erauso, colonial texts exploring Latin America staunchly supported an epic, masculine point of view. When considered at all, indigenous men and women alike lacked any voice altogether; even doña Marina, the literal “tongue” of Hernán Cortés, required Bernal Díaz del Castillo’s Historia verdadera de la conquista de Nueva España to achieve a lettered presence, albeit in the words of a European male writer in the end. The very first pages of Isabel Allende’s novel Inés del alma mía (Inés of My Soul) address this discursive void in a thoroughly deliberate manner. Introduced as “Crónicas de doña Inés Suárez,” Allende’s book ventures into a territory challenging hegemonic representations of subjugated indigenous populations of Latin America as well as European women involved in the conquest. While the “Crónica de las Indias” frequently reveals a distinctly hybrid character, the simultaneous multiplication of indigenous and Spanish subjects in Inés del alma mía promises a narrative that offers an innovative agency of the former in the context of the Latin American conquest.
Keywords: chronicle; Isabel Allende; Inés del alma mía; Inés Suárez